Bureaucrats Communication Model Based on Local Wisdom of Silih Simbeuh - Akmala Hadita; Mulyaningsih (SIASAT, 2022)
This study aims to develop a communication model based on local wisdom originating from Sundanese culture, namely Silih Simbeuh, which is carried out by bureaucrats to socialize their policies to the public. The method used is qualitative, with a survey approach – descriptive. Data were collected through interviews, observation, and documentation studies. 29 research informants were determined purposively. Data analysis was carried out through the stages of reduction, display, analysis, and concluding. The objects of research are three governors who actively use social media, namely Anis Baswedan (DKI Jakarta), Ridwan Kamil (West Java), and Ganjar Pranowo (Central Java). The results show that the use of social media can be an effective and efficient communication tool in disseminating policies, through increasing public participation. This is shown in the form of following social media accounts, comments, reposts, and other interactions. The results of other studies show that the communication model using social media based on the Silih Simbeuh concept has proven to be effective in minimizing potential conflicts between policymakers and citizens and between citizens. The research location is narrow, the respondents are limited, and the methods used do not allow for generalizations. Further research is needed with more comprehensive coverage of respondents and methods Silih Simbeuh's local wisdom values can minimize conflicts in the communication process between policymakers and the community